Effect of Bladder Distention Following Water Ingestion on Cardiac Autonomic Balance in Healthy Young Men - Seyed Mehran Hosseini; Hamid Sepehri (Golestan University Of Medical Sciences, 2019)
Background and objectives: Bladder filling and severe urgency to urinate may affect the cardiovascular system through viscero-visceral reflexes. In the cardiovascular system, post-micturition syncope is a well-known and clinically important consequence of this phenomenon. Despite the importance of such reflexes, limited numbers of studies have investigated the in vivo effects of bladder filling on the heart. The purpose of this study was to determine the effects of bladder filling through water ingestion on heart rate and the autonomic nervous system in healthy young men. Methods: This was a descriptive-analytical study performed on 20 healthy male volunteer students. Five minutes after voluntary bladder emptying, the electrodes were attached and heart rate was recorded in the sitting position in a controlled environment. After five minutes of adjustment, data collection was started at 1 KHz sampling frequency. Then, the participants continued drinking water until developing severe urgency to urinate. Heart rate was recorded at the peak of urgency and the data were compared with baseline values. All data were expressed as mean ± standard deviation. Statistical analyses of data were performed using SPSS 16 at significance level of 0.05. Results: Mean age, weight and height of the participants were 22.3 ± 3.466 years, 75.55 ± 15.5 kg and 175.8 ± 11.28 cm, respectively. Mean heart rate was 74±12.23 after the initial urination, 68.55±10.53 when feeling severe urgency to urinate and 66.3±10.87 after the second urination. The heart rate differed significantly between the three tested conditions (P<0.05). There was no significant difference in other parameters of heart rate variation including SDNN, RMSSD, RRM, PNN50, absolute and relative (normalized) low frequency and high frequency and their ratio (LF/HF). Conclusion: Bladder distension secondary to drinking water has no effect on the heart autonomic balance.